Schwartz's Principles of Surgery - Brunicardi, F. Charles (New York : McGraw-Hill, 2019)
Based on general surgery's cornerstone text, Schwartz's Principles of Surgery, this unmatched study guide provides everything you need to ace your exams, whether you're a medical student, a resident, or a practicing surgeon seeking recertification. Developed by some of the top minds in modern surgery, Schwartz's Principles of Surgery ABSITE and Board Review delivers the most current, authoritative perspectives on surgical practice. The board-style practice questions are accompanied by answers and comprehension-building rationales, ensuring a complete understanding of the material. Featuring hundreds of illustrations, photos, and tables, this is a resource for certification and recertification example review.
Includes bibliographical references and index.
HBK.
Keywords: American Board of Surgery -- Study guides. -- Examinations; Surgery -- Examinations, questions, etc; Surgery, Operative; Surgical Procedures, Operative; Examination Questions; Chirurgie -- Examens, questions, etc; Chirurgie opératoire.; Examinations; Surgery; Examinations; Study guides